Sleep Disorders' Prevalence and Impact on Academic Performance among Undergraduate Nursing Students in a Selected University, United Arab Emirates - Fatma M Ibrahim PhD; Rahma Nemer Salmi; Malak Anes Saif; Amani Mohammed (SAGE Publishing, 2024)
Introduction Throughout their academic pursuits, students may encounter various sleep-related issues, including insomnia, sleep apnea, hypersomnia, or sleep terror disorder. These disorders can profoundly impact their well-being, emotional state, and academic achievements. Objective This study, of significant relevance to the field of nursing and sleep disorders, aimed to investigate the prevalence of sleep disorders and their impact on academic performance among undergraduate nursing students in the United Arab Emirates. Methods A cross-sectional research method was implemented among 177 undergraduate nursing students. Two tools were used: Too I consisted of two parts: sociodemographic and academic performance classifications, whereas Tool II comprised the SLEEP-50 questionnaire. Results Our findings revealed that 30.6% of nursing students had one or more sleep disorders. Insomnia was the most prevalent among the nursing students (37.5%), followed by circadian rhythm (33.3%), narcolepsy (26.6%), sleep apnea and restless leg syndrome (25%), nightmares (22.2%), and sleepwalking (11.11%). There was a significant relation between restless leg syndrome and academic performance, while in linear regression analysis, it was found that the variable that most affects sleep is gender. Conclusion The implications of this study's findings are clear-nursing schools must intensify their efforts to raise awareness about the detrimental effects of sleep problems on academic performance. Furthermore, subsequent research is crucial to evaluate the execution of interventions aimed at preventing such disorders.